PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KOMITE AUDIT, DAN FAKTOR LAIN TERHADAP NILAI PERUSAHAAN - Nicholas Aditya; Indra Arifin Djashan (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to analyze the effect of firm size, liquidity, audit committee, company growth, board size, profitability, debt to asset ratio, firm age on firm value. The object in this research is manufacture companies listed on Indonesia Stock Exchange from 2018 to 2020 as the population. This research uses purposive judgement sampling method in selecting the sample. There are 70 companies, so the total data used was 210. This research uses multiple regression method for data analyst. The result shows that profitability, debt to asset ratio, and firm age have effect to firm value, but firm size, liquidity, audit committee, company growth, and board size have no effect to firm value